Rituximab Use in the Management of Childhood Nephrotic Syndrome - Kallash, Mahmoud; Smoyer, William E.; Mahan, John D. (Frontiers in Pediatrics, 2019)
Childhood nephrotic syndrome is a challenging and often persistent renal disorder, and its incidence varies between different ethnicities and regions. Corticosteroids have been the main treatment for decades and are effective in most children with idiopathic NS, although 10–15% of these children become steroid resistant. Furthermore, some initially steroid sensitive children follow a steroid dependent or frequently relapsing course and are therefore at increased risk for developing steroid toxicity. In such children, alternative immunosuppressive medications are used to induce and/or maintain remission of NS. One such drug, rituximab, is a monoclonal antibody directed against the B lymphocyte CD20 marker which induces depletion of B cells, and has shown promising results in the management of NS in children. In this review, we summarize recent studies on the efficacy and safety of rituximab in the different types of childhood nephrotic syndrome, the known and potential mechanisms of action of rituximab, its possible complications and side effects, and the available and potential biomarkers of rituximab activity.